If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 26 = -3x + 9x Combine like terms: -3x + 9x = 6x 26 = 6x Solving 26 = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 26 + -6x = 6x + -6x Combine like terms: 6x + -6x = 0 26 + -6x = 0 Add '-26' to each side of the equation. 26 + -26 + -6x = 0 + -26 Combine like terms: 26 + -26 = 0 0 + -6x = 0 + -26 -6x = 0 + -26 Combine like terms: 0 + -26 = -26 -6x = -26 Divide each side by '-6'. x = 4.333333333 Simplifying x = 4.333333333
| 5x(2x-8)-2=5(x-3)+3 | | 14.5=5.5h-2 | | w+6=-18 | | (4m-4m)= | | -15d-21=564 | | 5x+15=5x-15 | | 4(m-a)=6 | | 3-2x=5x+9 | | 5.50r+6p=51 | | (4x-6)(3x+6)= | | X^2+y^2-3x-10y=13 | | 5x^2+6x-36=-4 | | -2p=-24 | | f(x)=x+3y | | -9=3(x-6)+18 | | -x-5=x-15 | | -13=5(1+n)-2n | | (7a+15)= | | 2x+8y=560 | | -4(y-2y)+7=-4(5y-y)+2+19y | | 4=4+5n+-4n | | -7v-2-4v=9 | | -4w-4(5z-6w)-6z= | | 12(3.14)2= | | (5x+8)+6=(8+5x)+6 | | (2x^2)(x+4)=0 | | 2645+476v= | | 11-5=-4 | | -3b+3b=6 | | 11d+10=6d-2 | | 3(d-8)-5=9 | | 4730-j=2712 |